ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI PUS DALAM METODE KONTRASEPSI JANGKA PANJANG (MKJP) DI KECAMATAN LANGSA TIMUR TAHUN 2021 - Yulizar Yulizar; R. Kintoko Rochadi; Rinawati Sembiring; Donal Nababan; Mido Ester J. Sitorus; Toni Windra (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
One of the government's ways to overcome the growth rate and birth rate in Indonesia is through the family planning (KB) program. Long-term contraceptive methods are an effective method of delaying and spacing pregnancies, as well as stopping fertility. Therefore, the government is trying to increase the use of long-term contraceptives, but the fact is that the use of non-long-term contraceptives is higher than the use of long-term contraceptives. This study aims to determine and analyze the factors that influence EFA participation in the Long Term Contraceptive Method (MKJP). This type of research uses a cross sectional approach which will be carried out in the Langsa Timur District in 2021. The population in this study is all couples of childbearing age (PUS) who use contraception in the Langsa Timur sub-district, amounting to 2,261 people with a sample size of 96 respondents. . The results showed that the age variable had a value of p=0.009 (p<Î±); OR is 1.358, parity has a value of p=0.001; OR is 2,910, knowledge has a p value = 0.005; OR is 2.476, attitude has p value = 0.001; OR is 2,286, husband's support has p value = 0.030; OR is 2.452, and the role of health workers has a p value = 0.023; OR is 2,932. These results mean that the variables of age, parity, knowledge, attitude, husband's support, and the role of health workers have a significant influence on MKJP participation because they have a value (p<Î±). It is recommended to the Langsa City Health Office, especially for East Langsa District, to increase promotion of MKJP contraceptives and cooperate with related parties, such as the Family Planning and Women's Empowerment Agency (BKBPP) of Langsa City and religious leaders and local community leaders to increase MKJP coverage. ..